Legal Consequences of Cancellation of the Land Sale and Purchase Agreement by the Seller Consequences of Buyer Defaulting - Santoso Budi Nursal Umar; Doris Rahmat (Indonesian Journal Publisher, 2024)
This research aims to determine the process of canceling a land sale and purchase by the seller because the buyer defaulted, the legal consequences of canceling the land sale and purchase agreement by the seller because the buyer defaulted. The research method used in this research is descriptive analytical. The research results of the sale and purchase agreement process are valid and have binding force since an agreement is reached between the seller and the buyer. The sale and purchase agreement is based on the validity of the contract and other agreement principles. An agreement can be null and void (van rechtswege neiting) or can be canceled (vernietigbaar), if an agreement does not meet the requirements specified in accordance with Article 1320 of the Civil Code, namely if it does not fulfill subjective requirements (they agree to bind themselves, are competent to make an agreement) and objective conditions (a certain thing, a lawful cause). The legal consequences that arise for the buyer if they default, the buyer is required to pay compensation for losses suffered by the seller, pay court costs if sued in court, and fulfill the agreement if it continues